One‐Shot Intrablock Cross‐Linking of Linear Diblock Copolymer to Realize Janus‐Shaped Single‐Chain Nanoparticles. Issue 33 (8th July 2021) - Watanabe, Kodai; Kaizawa, Noya; Ree, Brian J.; Yamamoto, Takuya; Tajima, Kenji; Isono, Takuya; Satoh, Toshifumi
Abstract: Developing an efficient and versatile process to transform a single linear polymer chain into a shape‐defined nanoobject is a major challenge in the fields of chemistry and nanotechnology to replicate sophisticated biological functions of proteins and nucleic acids in a synthetic polymer system. In this study, we performed one‐shot intrablock cross‐linking of linear block copolymers (BCPs) to realize single‐chain nanoparticles (SCNPs) with two chemically compartmentalized domains (Janus‐shaped SCNPs). Detailed structural characterizations of the Janus‐shaped SCNP composed of polystyrene‐block‐poly(glycolic acid) revealed its compactly folded conformation and compartmentalized block localization, similar to the self‐folded tertiary structures of natural proteins. Versatility of the one‐shot intrablock cross‐linking was demonstrated using several different BCP precursors. In addition, the Janus‐shaped SCNP produce miniscule microphase‐separated structures. Abstract : A one‐shot intrablock cross‐linking protocol was demonstrated to achieve a rapid and facile synthesis of single‐chain nanoparticles (SCNPs) with two chemically compartmentalized domains (Janus‐shaped SCNPs) from the various diblock copolymers bearing one particular cross‐linkable functionality across the entire polymer chain. Janus‐shaped SCNP produce significantly small microphase‐separated structure.